Insight into the efficient catalytic conversion of biomass to EG and 1, 2-PG over W–Ni bimetallic catalyst. Issue 20 (19th March 2018) - Li, Meng-Qing; Ma, Yu-Long; Ma, Xiao-Xia; Sun, Yong-Gang; Song, Zhi
Abstract : Bimetallic supported catalyst (W-Ni/MSM) was proposed to improve capability of catalytic conversion and investigated reaction pathway of lignocellulose into ethylene glycol and 1, 2-propylene glycol. Abstract : In this work, a mesoporous silica microsphere (MSM) was selected as a support to prepare a bimetallic supported catalyst (15% W–5% Ni/MSM) by a co-impregnation method that was simple and easy to conduct. We wished to improve the capability of catalytic conversion of biomass into ethylene glycol (EG) and 1, 2-propylene glycol (1, 2-PG). 15% W–5% Ni/MSM was examined on microcrystalline cellulose (cellulose) and corn stalks in a one-pot catalytic process, and total yields of EG and 1, 2-PG reached up to 82.40 wt% and 62.60 wt%, respectively. This remarkable catalytic performance of W–Ni/MSM catalyst could be attributed to the synergistic effect between the active sites of Ni and W and the unique structure of MSM, which was suitable for mass transfer and metal loading. Based on physicochemical characterizations, the metal component was well-distributed on the surface of the MSM, and the metallic Ni, W and WO3 of the fresh catalyst were converted mainly into NiWO4 during the catalytic conversion of cellulose. To shed light on the reaction mechanism of the catalyzed hydrogenation of biomass, a possible process involving the formation of H x WO3 homogeneous catalysts, cellulose hydrolysis, C–C cleavage and hydrogenation conversion to 1, 2-PG and EG was illustrated. Furthermore, the reusability of W–Ni/MSM catalyst was tested and we explored the cause of decreased diols yields. In summary, this work provides important guidance to rationally design effective catalysts for biomass conversion.